2016
DOI: 10.1080/13588265.2016.1198000
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of in-plane mechanical performance of carbon/glass hybrid woven composite at different strain rates

Abstract: Woven composite has been increasingly employed in engineering applications undergoing complex loading conditions. For effective use of composite materials, it is essential to fully understand the mechanical behaviour of composite at different strain rates. In the present study, both in-plane tensile and compressive mechanical properties of a carbon/glass hybrid plain weave composite were experimentally investigated over the strain rate range from 0.001 to 1000 s ¡1 . High strain rate tests were carried out usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They used acoustic emission techniques to capture the transition of the material's failure modes and identified multiple failure mechanisms in the hybrid composite. Zhu et al 9 investigated the tensile and compressive dynamic properties of carbon/glass hybrid composite. They observed that the material's performance was sensitive to strain rate and loading direction.…”
Section: Introductionmentioning
confidence: 99%
“…They used acoustic emission techniques to capture the transition of the material's failure modes and identified multiple failure mechanisms in the hybrid composite. Zhu et al 9 investigated the tensile and compressive dynamic properties of carbon/glass hybrid composite. They observed that the material's performance was sensitive to strain rate and loading direction.…”
Section: Introductionmentioning
confidence: 99%
“…Strain rate effects of the composite materials are highly correlated with materials hardening factors that are highly influenced with the types of materials used, manufacturing process, surficial adhesion between fibre and matrix, fibre architecture, loading direction, and the range of applied strain rates. These factors have been discovered after testing the hybrid composite of carbon/glass at strain rates of 200, 600, and 1000 s −1 [9]. The investigation on the mechanical properties of glass fibre composites extensively done by previous researchers on the stress-strain profiles due to the temperature effect [10].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the metalworking, crash box component suffers a plastic deformation history which impresses the crashworthiness response. After the rolling process, sheet metals will be employed in the tension, bending, and stretching dies with varying loading paths and strain rates [10,11]. Hence, the plastic deformation history affects the crash box dynamic response, an issue considered by many scholars.…”
Section: Introductionmentioning
confidence: 99%